Fantastic Norway: Interview with Håkon Matre Aasarød - Håkon Matre Aasarød (Oz, 2009)
Fantastic Norway is a collaboration between Erlend Blakstad Haffner and Håkon Matre Aasarød. Founded in 2004, the firm balances a commercial office in Oslo with a nomadic public service component – a red caravan the firm drives across Norway to small towns they feel could use architectural consultation.